Counselling skills - Postings, Traci (Los Angeles : SAGE, 2022)
This counselling skills book will equip you with the necessary knowledge, skills and qualities to work with people in a range of different roles and settings. This book is an accessible guide to the BACP counselling skills competence framework for trainee counsellors and those using counselling skills as part of another professional role.
"British Association for Counselling and Psychotherapy"
Includes bibliographical references (pages 255-260) and index.
Keywords: Counseling